STUDENTS PERCEPTIONS OF THE IMPLEMENTATION OF BLENDED LEARNING METHOD IN ENGLISH LANGUAGE TEACHING (ELT) - Utin Dian Octavia; Aunurrahman Aunurrahman; Ageung Darajad (IKIP PGRI Pontianak, 2021)
AbstrakPenelitian ini bertujuan untuk mendeskripsikan persepsi siswa terhadap penerapan blended learning dalam English Language Teaching (ELT). Pelaksanaan blended learning di ELT baru dilaksanakan kurang lebih satu tahun dan pertama kali dilaksanakan di kelas sepuluh. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Kuesioner terbuka dibagikan kepada 116 siswa dari seluruh siswa SMAN 1 Selimbau yang mengikuti pelaksanaan blended learning dan dipilih dengan menggunakan teknik purposive sampling. Sementara itu, wawancara semi terstruktur dilakukan dengan guru bahasa Inggris yang menerapkan blended learning, untuk membandingkan data penelitian dari persepsi siswa. Untuk menganalisis data, peneliti menggunakan analisis tematik. Hasil analisis menunjukkan bahwa siswa memiliki pemahaman dasar tentang penerapan blended learning dalam English Language Teaching (ELT). Para siswa juga memiliki harapan yang tinggi terhadap penerapan blended learning, yaitu kedepannya penerapan metode blended learning di ELT dapat dilakukan secara berkesinambungan. Para siswa juga mengkritisi pelaksanaan blended learning dan memberikan saran agar dalam pelaksanaan blended learning sebaiknya memperhatikan segala sesuatunya.Kata Kunci: Persepsi Siswa, Blended Learning, Pengajaran Bahasa Inggris. Abstract This research aims to describe students' perceptions of the implementation of blended learning in English Language Teaching (ELT). The implementation of blended learning in ELT has only been carried out for approximately one year and was first implemented in the tenth grade. This research used a descriptive qualitative approach. An open-ended questionnaire was distributed to 116 students' from all students in SMAN 1 Selimbau who attended the implementation of blended learning and were selected using a purposeful sampling technique. Meanwhile, semi-structured interviews were conducted with English teachers who implemented blended learning, to compare research data from students' perceptions. To analyze the data, the researcher used thematic analysis. The results of the analysis show that the students have a basic understanding of the implementation of blended learning in English Language Teaching (ELT). The students also have a high expectation of the implementation of blended learning, that is, in the future, the implementation of the blended learning method in ELT can be carried out continuously. The students also criticized the implementation of blended learning and gave suggestions that in the implementation of blended learning it is better to pay attention to everything.Keywords: Students Perceptions, Blended Learning, English Language Teaching